Psychological Disorder Perilaku Abnormal: Mitos dan Kenyataan - Antonius Atosökhi Gea (Bina Nusantara University, 2013)
There are a variety of behaviors considered as a deviant behavior (abnormal behavior) because it is different to the behaviors generally accepted in the society. Behaviors considered deviant are determined based on certain criteria, used to assess a behavior as a deviant behavior. Behaviors considered abnormal are classified into specific or difference types. Thus, it is known the name of some kind of abnormal behaviors, in light and heavy level. Important question related to deviant behavior is: whether the symptoms of deviant behavior can be considered as a disease. There are different understandings of the past and the present time. From a medical standpoint (these days), symptoms of a deviant behavior are classified as a disease. If so, then there are actually quite a lot of people suffer from deviant behaviors, because the symptoms described as an abnormal behavior are found in many people, though in different levels.